Analisis Rasio Likuiditas Untuk Menilai Kinerja Keuangan Pada Perusahaan Sub Sektor Farmasi Di BEI - Nadila Nadila; Aris Munandar; Nafisa Nurrahmatiah (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
The liquidity ratio is a measurement of the ability of a company's assets to finance its short-term liabilities or debt. The liquidity ratio is a measurement of the ability of a company's assets to finance its short-term liabilities or debt. The research results show that the financial performance of Pharmaceutical Sub-Sector Companies on the BEI is based on the Current Ratio (CR) in the poor category and the financial performance of Pharmaceutical Sub-Sector Companies on the BEI is based on the Quick Ratio (QR) in the poor category.